BAGAIMANA KOMUNIKASI ANTARA PENGELOLA DENGAN PEMERINTAH DALAM MEMBANGUN CITRA DESTINASI KAMPUNG WISATA TEMATIK? - Indira Maulidia; Mariana Rista Ananda Siregar; Roni Jayawinangun (UNIVERSITAS PAKUAN, 2022)
This study aims to determine the role and communication relationship patterns of the Bogor City Department of Tourism and Culture (Disparbud) in establishing communication with the community around the Mulyaharja Tourism Village in managing tourism in their area. The theory of Relationship Management is used by researchers as an effort to systematize the analysis and discussion of the findings of this study. The design of this research is descriptive qualitative. Data collection techniques used include interviews, observation, documentation, and literature study. The results of the study indicate that the communication established by the Bogor City Department of Tourism and Culture to external parties which are the managers of tourist villages and the tourism driving group (Kompepar) is two-way. The communication pattern formed between internal and external parties is a secondary communication pattern, where the manager of the tourist village is a medium for conveying messages to Kompepar. The branding efforts carried out by the government and Kompepar, namely by marketing the Mulyaharja Thematic Tourism Village through social media such as Instagram and Youtube.